Challenges with hippocampal MR spectroscopy as a surrogate for pre-radiotherapy assessment of neurocognitive impairment in patients with brain metastasis - Selingerová, Iveta; Holíková, Klára; Chodúr, Tomáš; Hynková, Ludmila; Pospíšil, Petr; Bulik, Martin; Belanová, Renata; Šiffelová, Kamila; Koloušková, Ivana; Slávik, Marek; Burkoň, Petr; Hrstka, Roman; et al. (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
AIM: Patients with multiple brain metastases (BM) benefit from hippocampal-avoiding whole brain radiotherapy (HA-WBRT), the challenging and less available form of WBRT. This study explores potential of pre-radiotherapy (pre-RT) hippocampal magnetic resonance spectroscopy (MRS) measuring hippocampal neuronal density as an imaging surrogate and predictive tool for assessing neurocognitive functions (NCF). METHODS: 43 BM patients underwent pre-RT hippocampal MRS. N-acetyl aspartate (NAA) concentration, a marker for neuronal density (weighted by creatine (Cr) and choline (Cho) concentrations), and neurocognitive function (NCF) tests (HVLT and BVMT) performed by certified psychologists were evaluated. Clinical variables and NAA concentrations were correlated with pre-RT NCFs. RESULTS: HVLT and BVMT subtests showed pre-RT deterioration except for BVMT recognition. Significantly better NCFs were observed in women in HVLT subsets. Significantly higher NAA/Cr + Cho was measured in women (median 0.63 vs. 0.55; P=0.048) in the left hippocampus (no difference in the right hippocampus). In men, a positive correlation (0.51, P=0.018) between total brain volume and HVLT-TR, between left hippocampal NAA/Cr + Cho and HVLT-R (0.45, P=0.063), and between right hippocampal NAA/Cr + Cho and BVMT-recognition (0.49, P=0.054) was observed. In women, a borderline significant negative correlation was observed between left hippocampal NAA/Cr + Cho and BVMT-TR (-0.43, P=0.076) and between right NAA/Cr + Cho and HVLT-DR (-0.42, P=0.051). CONCLUSION: Borderline statistically significant correlations were observed with speculative interpretation underlying the challenges of hippocampal MRS as a surrogate for neurocognitive impairment. Further studies need to be done to ascertain the opportunities for imaging predictors of benefit from memory sparing radiotherapy.
Keywords: nádory mozku; Humans; neuropsychologické testy; lidé středního věku; Brain Neoplasms; Cranial Irradiation; Choline; kreatin; Female; Aged; dospělí; Hippocampus; senioři; lidé; kyselina aspartová; magnetická rezonanční spektroskopie; cholin; hipokampus; Creatine; Adult; Neuropsychological Tests; ženské pohlaví; Male; Middle Aged; Cognitive Dysfunction; Aspartic Acid; Magnetic Resonance Spectroscopy; mužské pohlaví; kognitivní dysfunkce; kraniální ozáření